Experimental evaluation of the effects of ingredients ratio, combination of slag and zeolite as Precursor and Emboss fiber on the strength characteristics of geopolymer mortar - V. Ghadaki; M. K. Sharbatdar (مهندسی عمران شریف, 2021)
About 7% of the total volume of carbon dioxide produced in the world belongs to cement plants. Therefore, it is necessary to look for suitable alternative materials that their mechanical characteristics are similar to or better than mortars made with OPC and also consider the concept of sustainable development and environmental protection. In this paper, the effects of ingredients ratio, combination of slag and zeolite as Precursor and adding Emboss fiber on the strength characteristics of geopolymer mortar has been investigated experimentally in three separate sections. The different parameters such as weight ratios of sand to slag, sodium silicate to sodium hydroxide in activator solution, concentration of sodium hydroxide solution, different volume percentages of Emboss fiber, and replacing a part of the slag with zeolite were considered and studied in three parts. In the first part, 18 mix designs including 180 specimens were casted to study the effect of ingredients ratios on 7-days and 28-days compressive strength. In the second part, 3 mixes designs were selected from the part 1 and considered as the second group including 105 specimens to measure the compressive strength and modulus of rupture. In the third part, a part of the slag in one of mix designs that was selected from part 1, was replaced with zeolite to study the effect of using combined slag-zeolite as Precursor to investigate 28-days compressive strength and modulus of rupture of the geopolymer mortar. 30 specimens were casted in part 3. Experimental results indicated that the reduction of the sand to slag ratio, the reduction of sodium silicate to sodium hydroxide ratio, the increase of sodium hydroxide molarity, and adding Emboss fiber, respectively, increased the compressive strength by 26, 6, 20, and 14%. The modulus of rupture of fiber specimens was increased up to 38% compared to non-fiber samples. Despite the significant reduction in the strength properties of geopolymer mortar containing zeolite, due to the large number of natural zeolite mines in our country (IRAN) and consequently easy access to this material, using a precursor composed of slag and zeolite could be a good idea.